Prevalence of precancerous lesions and other cervical abnormalities among internally displaced women in Benue State Nigeria (2024)
Introduction: visual inspection is a low-cost screening strategy that can be used to prevent cervical cancer in women. These techniques can improve screening health outcomes for internally displaced women (IDW) who have poor sexual and reproductive health and rights' behaviors and outcomes. This study aimed to determine the prevalence of precancerous lesions and other clinical features using a visual inspection with acetic acid (VIA) technique during a cervical cancer screening campaign in two internally displaced people (IDP) camps in Benue State, Nigeria. Methods: this was a cross-sectional study of 166 IDW who voluntarily participated in the study during a VIA cervical cancer screening campaign in two IDP camps in Benue State, Nigeria the screening was done by a group of qualified and trained healthcare workers and data was collected using a structured, pretested questionnaire. Results: a total of 99(60%) of the women had a first sexual experience at 16 years, while 78(47%) had more than 5 full-term pregnancies. Although only 72(43.4%) of the women acknowledged having more than one sexual partner, over 70% of the women stated that their sexual partner had another sexual partner. The prevalence of precancerous lesions among women was 10.8%. Smoking(p=0.003), age at menarche (p≤ 0.001) and sexual behaviors (p=0.009, p=0.004) were factors that had a statistically significant relationship with the presence of a precancerous lesion among the IDW. The study also highlights the high rate (95%) of cervicitis among the women and the relatively high rate (5.4%) of leukoplakia. Conclusion: the majority of IDW had sociodemographic and lifestyle characteristics that predisposed them to developing cervical cancer More targeted interventions aimed at improving the sociodemographic and lifestyle characteristics of IDW are recommended. In addition, there is a need to create awareness about cervical cancer among IDW and make screening available in camp facilities for early detection and management.